Seropositivity in blood donors and pregnant women during the first year of SARS‐CoV‐2 transmission in Stockholm, Sweden. (18th May 2021) - Castro Dopico, X.; Muschiol, S.; Christian, M.; Hanke, L.; Sheward, D. J.; Grinberg, N. F.; Rorbach, J.; Bogdanovic, G.; Mcinerney, G. M.; Allander, T.; Wallace, C.; Murrell, B.; et al.
Abstract: Background: In Sweden, social restrictions to contain SARS‐CoV‐2 have primarily relied upon voluntary adherence to a set of recommendations. Strict lockdowns have not been enforced, potentially affecting viral dissemination. To understand the levels of past SARS‐CoV‐2 infection in the Stockholm population before the start of mass vaccinations, healthy blood donors and pregnant women ( n = 5, 100) were sampled at random between 14 March 2020 and 28 February 2021. Methods: In this cross‐sectional prospective study, otherwise‐healthy blood donors ( n = 2, 600) and pregnant women ( n = 2, 500) were sampled for consecutive weeks (at four intervals) throughout the study period. Sera from all participants and a cohort of historical (negative) controls ( n = 595) were screened for IgG responses against stabilized trimers of the SARS‐CoV‐2 spike (S) glycoprotein and the smaller receptor‐binding domain (RBD). As a complement to standard analytical approaches, a probabilistic (cut‐off independent) Bayesian framework that assigns likelihood of past infection was used to analyse data over time. Setting: Healthy participant samples were randomly selected from their respective pools through Karolinska University Hospital. The study was carried out in accordance with Swedish Ethical Review Authority: registration number 2020–01807. Participants: No participants were symptomatic at sampling, and blood donors were all over the age of 18. No additional metadata were available from the participants. Results: Blood donors and pregnant women showed a similar seroprevalence. After a steep rise at the start of the pandemic, the seroprevalence trajectory increased steadily in approach to the winter second wave of infections, approaching 15% of all individuals surveyed by 13 December 2020. By the end of February 2021, 19% of the population tested seropositive. Notably, 96% of seropositive healthy donors screened ( n = 56) developed neutralizing antibody responses at titres comparable to or higher than those observed in clinical trials of SARS‐CoV‐2 spike mRNA vaccination, supporting that mild infection engenders a competent B‐cell response. Conclusions: These data indicate that in the first year since the start of community transmission, seropositivity levels in metropolitan in Stockholm had reached approximately one in five persons, providing important baseline seroprevalence information prior to the start of vaccination. Abstract :